Dual language statistical word segmentation in infancy: Simulating a language‐mixing bilingual environment. Issue 3 (23rd November 2020) - Tsui, Angeline Sin Mei; Erickson, Lucy C.; Mallikarjunn, Amritha; Thiessen, Erik D.; Fennell, Christopher T.
Abstract: Infants are sensitive to syllable co‐occurrence probabilities when segmenting words from fluent speech. However, segmenting two languages overlapping at the syllabic level is challenging because the statistical cues across the languages are incongruent. Successful segmentation, thus, relies on infants' ability to separate language inputs and track the statistics of each language. Here, we report three experiments investigating how infants statistically segment words from two overlapping languages in a simulated language‐mixing bilingual environment. In the first two experiments, we investigated whether 9.5‐month‐olds can use French and English phonetic markers to segment words from two overlapping artificial languages produced by one individual. After showing that infants could segment the languages when the languages were presented in isolation (Experiment 1), we presented infants with two interleaved languages differing in phonetic cues (Experiment 2). Both monolingual and bilingual infants successfully segmented words from one of the two languages—the language heard last during familiarization. In Experiment 3, a conceptual replication, we replicated the findings of Experiment 2 with a different population and with different cues. As before, when 12‐month‐old monolingual infants heard two interleaved languages differing in English and Finnish phonetic cues, they learned only the last language heard during familiarization. Together, our findings suggest that segmenting words in a language‐mixing environment is challenging, but infants possess a nascent ability to recruit phonetic cues to segment words from one of two overlapping languages in a bilingual‐like environment. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=92pNcpxZguw . Abstract : We tested infants at 9.5 (Experiment 1, 2) and 12 months (Experiment 3a and 3b) with a dual‐input statistical segmentation task that mimics a language mixing bilingual context. We found that infants can use subtle phonetic cues to successfully segment words from one of the two artificial languages. This finding also suggests that word segmentation in a language mixing context can be difficult but not impossible.